The Development of Vocational English Learning Methods and Media at Vocational Adaptive Training in BBPPMPV BOE Malang - Suherman, Jojon (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2021)
Abstract : Education and Training of Vocational High School English teachers using the vocational adaptive model aimed at increasing English competence of using vocational content. The objective of this study was to develop the vocational adaptive training materials consisting of the development of vocational English methods and media. The research method was development research and conducted at Centre of Development and  Quality Assurance for Vocational Education in Automotive and Electronic Sector (BBPPMPV BOE) Malang.The reseach results showed that the development of vocational English methods consisting of bilingual method, song method and tutor method received responses from the vocational English teachers with an average score of 4.8 in the category of very useful, very interesting, and very innovative. The development vocational English media consisting of quality standard video (QSV), vocational English dictionary (VED) and learning aid box (LAB) received responses from the vocational English teachers with an average score of 5.0 in the category of very useful, very interesting, and very innovative for teaching and learning English at Vocational High School.Key words: Vocational Adaptive, vocational English methods, vocational English media